FORMATION OF THE RAW MATERIAL BASE AND MEANS OF PRODUCTION FOOD INDUSTRY OF UKRAINE - Приліпко, Тетяна; Федорів, Віктор; Косташ, Володимир (Modern engineering and innovative technologies, 2023)
Agricultural raw materials are distinguished by certain features that significantly affect the activities of food industry enterprises. These resources are renewable, multi-component, interchangeable, seasonal, not very transportable, require economical u